Pengaruh Kedisplinan, Etos Kerja dan Kompetensi Terhadap Kinerja Pegawai Perusahaan Daerah Air Minum Kota Probolinggo - M. Saifullah; Titik Musriati; Agung Yatiningrum (Universitas Panca Marga, 2024)
The aim of the study was to find out whether the influence of work discipline, Work Ethics and competence has a partial effect on the performance of the employees of the Regional Drinking Water Company (PDAM) in Probolinggo City. The type of research used is descriptive quantitative, while the respondents in this study were employees of the Regional Drinking Water Company (PDAM) in Probolinggo City. The data collection method used saturated sampling, and obtained 69 respondents and a linear regression analysis tool using the SPSS 26 application. The methods of collecting information used in the research were: interviews, documentation and questionnaires. Partially, it affects the performance of employees of the Probolinggo Municipal Water Supply Company (PDAM). Results of the t (partial) test show that there is a positive and significant influence of work discipline and competency variables on the performance of employees of the Probolinggo Regional Drinking Water Company (PDAM).